The Effectiveness of Pedagogical Competency on the Performance of Certified Teachers at SMA Negeri 8 Lubuk Linggau - Sari, Fatma; Charli, Leo; Sulistiyono, Sulistiyono (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the influence of pedagogical competence on the performance of certified teachers at SMA Negeri 8 Lubuk Linggau. Pedagogical competence is a fundamental aspect that must be possessed by every educator in order to improve the effectiveness of the learning process and student learning outcomes. The research method used is quantitative with a descriptive correlational approach. Data were collected through questionnaires distributed to certified teachers, and analyzed using simple linear regression techniques to see the relationship between pedagogical competence and teacher performance. The results of the study indicate that there is a significant influence between pedagogical competence on the performance of certified teachers, where increasing pedagogical competence is directly proportional to increasing teacher performance in carrying out their professional duties. This finding indicates that efforts to improve pedagogical competence, both through training and continuous professional development, can contribute positively to the quality of education at SMA Negeri 8 Lubuk Linggau.